PSYCHO-SOCIAL EXPERIENCES OF PERINATALLY HIV-INFECTED ADOLESCENTS RESIDING IN CHILD AND YOUTH CARE CENTRES IN SOUTH AFRICA - Mavangira, Vimbai; Raniga, Tanusha (Social Work/Maatskaplike Werk, 2015)
The psycho-social impact of HIV on perinatally infected children has been overlooked by policy makers internationally and nationally. This study explored the psycho-social experiences of perinatally HIV-infected adolescents who were residing in child and youth care centres in Gauteng in South Africa. The article adopts a social constructionist lens to discuss their biographical profile as well as four themes: knowledge and feelings towards mother; dealing with secrecy and disclosure; the way social networks affect treatment adherence; and interactions with health and social services. The paper concludes with some suggestions for health and social service professionals to help these adolescents navigate through this phase of their lives.